Conversational Discourse Analysis Turn- Taking on an English Podcast - Saadah, Halimatus; Yuli Setyaningrum, Erma; Khoirot Daulay, Irma (Universitas Nusantara PGRI Kediri, 2024)
The use of turn-taking strategy is crucial in understanding the dynamics of conversation. This study aims to find out the turn-taking strategy used and how it impacts the communication process in English podcast video. This research uses descriptive qualitative and the object of research is a video podcast with analysis using Stenstroom theory. The results showed that taking over strategy was used the most, followed by promoting and appealing strategy. Other strategies such as starting up, overlapping, filled pauses & verbal fillers, and repetition of words were also recorded with lower frequency of use. However, no use of interrupting, repair, and giving up strategies in the conversations were observed. Based on the results of this study, it indicates a preference for the smooth flow of conversation in the communication process.